2018
DOI: 10.1002/ana.25267
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical relationship between live‐attenuated Japanese encephalitis vaccination and childhood onset myasthenia gravis

Abstract: ObjectiveThe incidence of childhood onset myasthenia gravis (CMG) in China is higher than that in other countries; however, the reasons for this are unclear.MethodsWe investigated the clinical and immunological profiles of CMG, and assessed the potential precipitating factors. For the mouse studies, the possible implication of vaccination in the pathogenesis was explored.ResultsIn our retrospective study, 51.22% of the 4,219 cases of myasthenia gravis (MG) were of the childhood onset type. The cohort study unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Annual influenza vaccination with inactivated vaccine is recommended. A recent study, suggested an association between a live-attenuated Japanese encephalitis vaccine and the high prevalence rate of JMG in China ( 36 ). The hypothesis was supported by a mouse model but has not been replicated by other groups and at this time, we would not contradict the use of live-attenuated vaccines where required.…”
Section: Treatment Of Jmgmentioning
confidence: 99%
“…Annual influenza vaccination with inactivated vaccine is recommended. A recent study, suggested an association between a live-attenuated Japanese encephalitis vaccine and the high prevalence rate of JMG in China ( 36 ). The hypothesis was supported by a mouse model but has not been replicated by other groups and at this time, we would not contradict the use of live-attenuated vaccines where required.…”
Section: Treatment Of Jmgmentioning
confidence: 99%
“…HLA DRw9 and DRw13 were strongly associated with Japanese MG [31], Bw46DR9 with Chinese [27,65], DQ8 and DR3 with Caucasian, and DR5 with African descents [66]. Besides, environmental factors may play as a trigger to activate the autoimmunity by way of molecular mimicry, supra-antigen or by-stander mechanism [17]. In all, CMG is a clinical entity with worldwide heterogeneity concerning the clinical presentations and the responses to therapy.…”
Section: The Possible Reasons For the Chinese Cmgmentioning
confidence: 99%
“…Unfortunately, the epidemiology of MG is generally lacking in China, and a survey in Yiyang county in Hunan Province in 1986 discovered 60 MG patients in 590,000 residents (incidence was 10/100,000), with CMG 48 cases (80%) [16]. The Chinese hospital-based reports stated that CMG patients were estimated to account for more than 50% of the MG population, with a peak of onset age before 10 years, mainly aged 2-5 years [4][5][6]17].…”
Section: Demographic Differencesmentioning
confidence: 99%
“…A recent investigation, exploring the molecular and clinical relationship between childhood-onset myasthenia gravis (CMG) and live-attenuated Japanese encephalitis vaccination (LA-JEV), implicated vaccinations in the development of MG, after excluding genetic factors and viral infection (60). Exposing BALB/c mice to a group of Chinese planned immunization programs, researchers found LA-JEV can cause MG-like symptoms in the mice (60).…”
Section: The Safety Of Vaccination In Mg Would Vaccination Trigger Mg?mentioning
confidence: 99%